Viscosity effects on sand flow regimes and transport velocity in horizontal pipelines - Yeung, Hoi; Yan, Wei; Al-Lababidi, Salem; Zorgani, E.; Fairhurst, C. P.; Al-Awadi, H. (Elsevier, 2017)
Solids transport in multiphase systems is one of the issues under the umbrella of ‘‘flow assurance.’ But unlike issues such as waxes and hydrates, solids transport has received relatively little interest to date. The overall aim of this research was to investigate the fluid viscosity effects on sand particle transport characteristics in pipelines. Investigations were conducted using a 3-inch test facility for oil and a 4- inch flow loop for water and CMC experiments. Three oil viscosities were used including 105 cP, 200 cP and 340 cP. The sand used had a density of 2650 kg/m3 and a median diameter of 0.2 mm. The sand loadings were 50 lb/1000 bbl and 200lb/1000bbl. Based on the King et al (2000) sand minimum transport condition definition, the sand transport velocity for water, CMC solutions and oil (105 cP, 200 cP and 340 cP) were determined by visual observation and camera. The observed sand/oil flow regimes were compared. For oil/sand tests, it was observed that the dominant regime when approaching the critical sand transport velocity was the sliding sand bed, sand dunes were notably absent. However, for water and 7 cP CMC solution, sand dunes and sliding sand bed regimes were observed when approaching the sand transport velocity. For 20cP CMC solution, it was observed that the sand particles in the region between the main dunes were very active compared to those within the dunes.